2005
DOI: 10.1051/0004-6361:20042305
|View full text |Cite
|
Sign up to set email alerts
|

Three-micron spectra of AGB stars and supergiants in nearby galaxies

Abstract: Abstract. The dependence of stellar molecular bands on the metallicity is studied using infrared L-band spectra of AGB stars (both carbon-rich and oxygen-rich) and M-type supergiants in the Large and Small Magellanic Clouds (LMC and SMC) and in the Sagittarius Dwarf Spheroidal Galaxy. The spectra cover SiO bands for oxygen-rich stars, and acetylene (C 2 H 2 ), CH and HCN bands for carbon-rich AGB stars. The equivalent width of acetylene is found to be high even at low metallicity. The high C 2 H 2 abundance ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(136 citation statements)
references
References 56 publications
14
121
1
Order By: Relevance
“…This may explain the remarkable strength of the molecular bands seen in the optical spectra of dust-enshrouded M-type AGB stars as well as in the optical and near-IR spectra of dustenshrouded carbon stars in the LMC (van Loon et al 1999a;Matsuura et al 2002Matsuura et al , 2005.…”
Section: The Hertzsprung-russell Diagram Of Dust-enshrouded Agb Starsmentioning
confidence: 92%
“…This may explain the remarkable strength of the molecular bands seen in the optical spectra of dust-enshrouded M-type AGB stars as well as in the optical and near-IR spectra of dustenshrouded carbon stars in the LMC (van Loon et al 1999a;Matsuura et al 2002Matsuura et al , 2005.…”
Section: The Hertzsprung-russell Diagram Of Dust-enshrouded Agb Starsmentioning
confidence: 92%
“…The model photosphere has a C/O ratio of 1.3. While this value is typical for Galactic Miras, the C/O ratio may be higher for Magellanic Cloud carbon stars (see, e.g., Matsuura et al 2005;Stanghellini et al 2005), which would change the optical depth due to increased molecular opacity. However, since we are limited by the small number of model photospheres available, we ignore these effects.…”
Section: Central Starmentioning
confidence: 94%
“…An accurate determination of the gas:dust ratio is still to be made for LMC carbon stars. Some observational and theoretical studies (e.g., Matsuura et al 2005;Wachter et al 2008) indicate that the carbon star gas:dust ratio may not be metallicity dependent. In fact, recent studies (Groenewegen et al 2007;Wachter et al 2008;Mattsson et al 2008) have found that the mass-loss rates of carbon stars may not be metallicity dependent.…”
Section: Dust Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuura et al 2005;Dijkstra et al 2005). Nevertheless, Speck et al (2000) found differences in the dust composition of RSG and AGB stars, the former often exhibiting Ca-Al-rich silicates instead of magnesium silicates.…”
Section: Introductionmentioning
confidence: 97%